How Depressive Symptomatology influence Productivity and Quality of Life: A Moderated Mediation Model - Lopes, Sara; Ferreira, Aristides I; Passos, Ana (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
This study examines the relationship between depressive symptomatology, productivity despite sickness presence and information processing in quality of life, by testing a moderated mediation model. Therefore, we intend to test if productivity despite sickness presence influences the relationship between depressive symptoms and quality of life and also if this relation is conditional upon levels of information processing speed. We would like to understand if depressive symptoms will have greater impact on an individual’s productivity when he/she also has higher levels of processing speed, and if that relationship will affect quality of life. The role played by cognitive variables in the relationship between depression, workforce performance and quality of life remains unclear (Baune et al., 2010; McIntyre et al., 2015; Cotrena, et al., 2016). Investigations in this area are needed, in order to provide better treatment and management practices of depressive symptoms in the workplace, which currently focuses on reducing mood-related symptoms, and not in cognitive performance (Baune et al., 2010). Data were collected from 231 participants (58% female) aged between 20 and 69 who completed a neuropsychological test and self-reported measures. A regression-based bootstrapping approach was used to examine the indirect effect of depressive symptoms on quality of life through productivity despite sickness presence and the moderating role of processing speed in the association between depressive symptomatology and productivity despite sickness presence. Results revealed a significant indirect effect and a significant moderation effect. The association between depressive symptoms and productivity despite sickness presence was moderated by information processing speed only in their medium and high levels. However, the results of the moderated mediation model were not statistically significant. Our findings suggest that individuals with higher levels of processing speed may have more difficulty in focusing on work without being distracted by health problems. The present investigation has made a significant contribution to the existing literature about cognitive function and productivity in workers with depressive symptomatology and its effects on their quality of life. To our knowledge, this is the first time that cognitive variables are tested as a moderator between the relationship of depressive symptoms and quality of life through a productivity measure. We hope these results contribute to the development of organizational interventions which target the specific needs of patients with different cognitive requirements, based on the management of productivity and quality of life